Diversity of Snakes in Rajegwesi Tourism Area, Meru Betiri National Park - Raharjo, Aji Dharma; Hakim, Luchman (Graduate School, Universitas Brawijaya, 2015)
Rajegwesi tourism area is one of the significant tourism areas in Meru Betiri National Park, East Java, Indonesia. The area rich in term of biodiversity which are potential for developed as natural tourism attraction. Â The aim of this study is to identify snakes species diversity and its distribution in Rajegwesi tourism area. Field survey was done in Rajegwesi area, namely swamps forest, residential area, rice fields, agriculture area (babatan), resort area, and Plengkang cliff. This study found some snakes, encompasses Colubridae (10 species), Elapidae (four species), and Phytonidae (one species). There are Burmese Python (Python reticulatus), Red-necked Keelback (Rhabdophis subminiatus), Painted Bronzeback Snake (Dendrelaphis Pictus), Black Copper Rat Snake (Coelognathus flavolineatus), Radiated Rat Snake (C. radiatus), Striped Keelback (Xenochrophis vittatus), Checkered Keelback (X. piscator), Spotted Ground Snake (Gongyosoma balioderius), Gold-ringed Cat Snake (Boiga dendrophila), Common Wolf Snake (Lycodon capucinus), Banded Wolf snake (L. subcinctus), Cobra (Naja sputatrix), King Cobra (Ophiophagus hannah), Malayan Krait (Bungarus candidus), and Banded Krait (B. fasciatus) was found. These snake habitats distributes at 21 coordinate points. Keywords: conservation, ecotourism, snakes.